"Is it depression, or am I the problem, it's me?" a multimodal analysis on the framing of depression in Psych2Go's Youtube videos - Villafuerte, Michelle Anne Mendoza
This study examines YouTube as a new medium for communicating and sharing information on mental health issues. Specifically, it analyzes how depression is framed in Psych2Go's YouTube videos. This study aims to analyze how Psych2Go's YouTube videos utilize audio-visual elements to frame information on depression.